Peterson's graduate programs in the business, education, health, information studies, law and social work (Thomson Peterson's, 2008)
Directory of institutions with programs in business, education, health, onformaton stidies, law, & social work, academic and professional programs in business, acade,ic and professnional in education, academic and professional programs in the health-related, academic and professional programs in law.